Blue Jasmine - Allen, Woody (The New York time, 2013)
After everything in her life falls to pieces, including her marriage to wealthy businessman Hal, elegant New York socialite Jasmine moves into her sister Ginger's humble apartment in San Francisco to try to pull herself back together again.